A atuação das Chatas Artilhadas no decorrer da Guerra do Paraguai - Aldeir Isael Faxina Barros (Navigator)
This article aims to demonstrate the use of artillery barrage during the Paraguayan War (1864-1870) since its debut on the battlefield, through the use of the same by the Brazilian Navy and the closure of its operation due to changes in the characteristics of struggles, taken after the abandonment of Humaitá fortress. The main battles and events that made up this new style of combat are presented in chronological order. Their strengths and weaknesses are highlighted in the course the battles that took place on the Paraná and Paraguay rivers.